Combined with ticagrelor, 50 mg aspirin daily can reduce bleeding events without increasing ischemic risk compared with 75–100 mg aspirin daily in coronary artery disease patients: insights from the TIFU (Ticagrelor in Fuwai Hospital) study. (17th August 2020) - Li, Jiannan; Sheng, Zhaoxue; Tan, Yu; Liu, Chen; Zhou, Peng; Zhou, Jinying; Chen, Runzhen; Chen, Yi; Song, Li; Zhao, Hanjun; Yan, Hongbing
Abstract: Patients treated with ticagrelor and aspirin usually suffer from bleeding events, especially mild bleeding which is one of the main factors reducing patients' adherence to ticagrelor. The objective of this study is to investigate the efficacy and safety of ticagrelor combined with a lower dose of aspirin (50 mg) than that recommended by guidelines (75–100 mg). In this study, we prospectively enrolled 1220 patients who take ticagrelor in the hospital. After excluding the patients who did not take ticagrelor after discharge or lost to follow-up, the remaining 1066 patients were divided into two aspirin dose groups: 75–100 mg ( n = 744) and 50 mg ( n = 322). The rates of major adverse cardiovascular events (MACEs), bleeding events and ticagrelor adherence were compared between the two groups. MACEs risk was not significantly different between the two groups (OR = 0.563, 95% CI: 0.244–1.300, P = .179). However, 50 mg aspirin was associated with a lower risk of any Bleeding Academic Research Consortium (BARC) bleeding events (OR = 0.605, 95% CI: 0.399–0.713, P = .001), also lower BARC bleeding events (OR = 0.639, 95% CI: 0.468–0.872, P = .005). Moreover, lower-dose aspirin was associated with a lower rate of ticagrelor withdrawal (OR = 0.459, 95% CI: 0.279–0.754, P = .002), mainly because of the decrease in ticagrelor withdrawal due to bleeding (OR = 0.378, 95% CI: 0.156–0.916, P = .031). After propensity score matching (PSM), a total of 317 patients in each group were matched. The MACEs composite was not significantly different between the two matched groups and 50 mg aspirin was associated with a lower risk of bleeding events and low ticagrelor withdrawal before and after multivariate adjustment. In conclusion, among patients who took ticagrelor (90 mg twice daily), 50 mg aspirin daily is associated with a lower rate of bleeding events and ticagrelor withdrawal but does not increase the MACE risk compared with 75–100 mg aspirin daily.